Formulation and Evaluation of Transdermal Patches of Baclofen - Patil, Bhagyashree S.; Sarkar, Tanushree; Raju, Tina; Bhutkar, M. A.; Mohite, S. K. (Asian Journal of Pharmaceutical Research and Development, 2014)
Transdermal drug delivery systems are becoming more popular in the field of modern pharmaceutics. The present study was carried out to develop matrix type transdermal patches containing Baclofen with different ratios of HPMC (hydroxyl propyl methyl cellulose) & EC (ethyl cellulose) by solvent casting method. Propylene glycol 3% is used as plasticizer & span 80 is used as permeation enhancer. The physicochemical compatibility of the drug and the polymers studied by infrared spectroscopy suggested absence of any incompatibility. Formulated transdermal films were physically evaluated with regard to thickness, weight variation, drug content, flatness, folding endurance moisture. All prepared formulations indicated good physical stability. In-vitro permeation studies of formulations were performed by using Franz diffusion cells.It shown that drug release follows zero order and the mechanism of release is diffusion from the polymer. The results suggested no physicochemical incompatibility between the drug and the polymers. Blank films were prepared and evaluated characteristics like smoothness and flexible. Further drug loaded films were prepared and evaluated for thickness, percentage flatness, tensile strength, weight uniformity, drug content,moisture content, moisture uptake, swelling index, water vapourtransmission, skin irritation and invitro-drug permeation study.